Ureteropelvic junction obstruction in infants: Open or minimally invasive surgery? A systematic review and meta-analysis - Valentina Cascini; Giuseppe Lauriti; Giuseppe Lauriti; Dacia Di Renzo; Maria Enrica Miscia; Maria Enrica Miscia; Gabriele Lisi; Gabriele Lisi (Frontiers Media S.A., 2022)
IntroductionThe historical gold standard treatment for ureteropelvic junction obstruction (UPJO) was the open Anderson-Hynes dismembered pyeloplasty (OP). Minimally invasive surgery (MIS) procedures, including laparoscopic pyeloplasty (LP) and robot-assisted laparoscopic pyeloplasty (RALP), have been reported to achieve better outcomes (i.e., decreased morbidity, reduced postoperative pain, superior esthetic results, and shortened length of hospital stay, LOS), with a success rate similar to OP. The main limitation of the MIS approach is the age and weight of patients, limiting these procedures to children >1 year. This study aims to evaluate the feasibility and benefits of MIS pyeloplasty compared to OP to surgically treat UPJO in children <1 year of age.Materials and methodsA systematic review was independently performed by two authors. Papers comparing both techniques (MIS pyeloplasty vs. OP) in infants were included in the meta-analysis. Data (mean ± DS or percentage) were analyzed using Rev.Man 5.4 A p < 0.05 was considered significant.ResultsNine studies (eight retrospective and one prospective) meet the inclusion criteria. A total of 3,145 pyeloplasties have been included, with 2,859 (90.9%) OP and 286 (9.1%) MIS. Age at operation was 4.9 ± 1.4 months in OP vs. 5.8 ± 2.2 months in MIS, p = ns. Weight at surgery was 6.4 ± 1.4 kg in OP vs. 6.9 ± 1.4 kg in MIS, p = ns. Operative time was 129.4 ± 24.1 min for OP vs. 144.0 ± 32.3 min for MIS, p < 0.001. LOS was 3.2 ± 1.9 days for OP vs. 2.2 ± 0.9 days for MIS, p < 0.01. Postoperative complications were present in 10.0 ± 12.9% of OP vs. 10.9 ± 11.6% in MIS, p = ns. Failure of surgery was 5.2 ± 3.5% for OP vs. 4.2 ± 3.3% for MIS, p = ns.ConclusionThe development of miniaturized instruments and technical modifications has made MIS feasible and safe in infants and small children. MIS presented a longer operative time than OP. However, MIS seemed effective for treating UPJO in infants, showing shortened LOS compared to OP. No differences have been reported with regard to the incidence of postoperative complications and failure of pyeloplasty. Given the low quality of evidence of the meta-analysis according to the GRADE methodology, we would suggest limiting MIS procedures in infants to only those high-volume centers with experienced surgeons.